Multiparameter collaborative optimization of the vibrating screen based on the behavior of oil sunflower seed penetrating screen holes - Wei, Wenbo; Li, Jianchang; Hao, Jianjun; Xiao, Maohua; Zhang, Huiju (International Journal of Agricultural and Biological Engineering, 2024)
The behavior of oil sunflower seeds penetrating screen holes is an important factor that affects the screening performance of oil sunflower seeds. In this study, a double-deck reverse-motion vibrating screening device for oil sunflower seed screening was designed. The force condition and motion law of the oil sunflower seeds on the screen surface were analyzed. This study compared the effect of particle filling amount of discrete element model of oil sunflower seeds on the simulation effects. The screening process was numerically simulated using the coupled Discrete Element Method and Multibody Dynamics (DEM-MBD) technique with the screening percentage of oil sunflower seeds as the index. The influence of the operating parameters of the vibrating screen on the screening effect was analyzed using a multiparameter collaborative optimization scheme. The results of this study can provide a reference for the numerical simulation of crop screening behavior and the development of screening devices. Keywords: oil sunflower seeds, screening analysis, DEM-MBD, discrete element method, response surface analysis DOI: 10.25165/j.ijabe.20241701.8111 Citation: Wei W B, Li J C, Hao J J, Xiao M H, Zhang H J. Multiparameter collaborative optimization of the vibrating screen based on the behavior of oil sunflower seed penetrating screen holes. Int J Agric & Biol Eng, 2024; 17(1): 49-58.